Islamic ethics in search: an analysis - Abdus Salam, Yunus Olatoke; Ali, Mohd Mumtaz (Globeedu Group, 2019)
There is no any iota of uncertainty that ethics occupies an integral part of man as a distinct creature honored to be the vicegerent on earth. The issue of ethics is as old as man on earth. From the dawn of civilizations, scholars (philosopher and thinkers) have approached the concept of ethics differently with no substantial unanimity reached. This article is an attempt to address ethics in an Islamic perspective. With the aid of an exploratory method, the study delved into the divine revelations (the Qur’an and Sunnah) and the interpretations of Islamic philosophers and intellectuals with regards to the concept of ethics. The findings showed that the majority of Islamic scholars view ethics as morality, while others understand it as the intellectual power with which man distinguishes between the nobles and vices. Moreover, through the study of concept of ethics, its scope, significance, principles, sources and characteristics, the divine revelations (the Qur’an and Sunnah) were found as the original sources of ethics.